DAYA TARIK ENDORSER NOAH TERHADAP BRAND IMAGE IKLAN KARTU XL: Studi Kuantitatif tentang Pengaruh Daya Tarik NOAH terhadap Brand Image Iklan Kartu XL di kalangan Mahasiswa Angkatan 2011 Universitas Sahid Surakarta - Retnaningtyas, Ester; Hastasari, Chatia; Pratiwi, Dyah Retno (JURNAL KOMUNITAS, 2014)
Nowadays, almost all of television commercialsuseartistsasendorser. The endorser is selected based on its attraction. They has a duty inintroducing the brand of a product. XL is one of the advertisement which use artist as an endorser. XL uses NOAH as an endorser because NOAH is considered having capability in creating brand image XL. The success in building the brand image is also determined by consumer perceptions of endorser who became icon is in the advertisement. Therefore, this research focus on analysis of is there any influence of NOAH attraction to brand image of XL advertisement among Sahid Surakarta University student class 2011.. The populations of this study is allof students inclass 2011 at Sahid Surakarta University. The total number of student is 295. Where as, the sampling techniques was used a simple random sampling (the taking of sample from population was randomly without regard to the existing strata in the population). This research used respondence’s questionnaire as the primary data. Meanwhile, in analizing influence of NOAH attraction to brand image of XL advertisement among Sahid Surakarta University student class 2011 was use Rank-Order Correlation. The Results of this studyshows that results Spearmen's coefficient Rho=0.426 and p-value of 0.000. Thus,p-value less than 0.05 it means that there is significant influence of NOAH attraction to brand image of XL advertisement among Sahid Surakarta University student class 2011.